The Influence of Blanching and Drying Process Towards Extract of Bioactive Compounds in Solanum Torvum and its Antioxidant Activities - Nunuk Helilusiatiningsih; Sumarji; Rizky Arief Shobirin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Eggplant Pokak has potential to be developed into processed products that contain antioxidant biocytic compounds. The purpose of this research was to analyze the bioactive compounds in Solanum torvum which were treated with blanching and various types of drying. The research method used quantitative analysis of antioxidant compounds against the treatments tested. The results showed that the analysis of bioactive compounds which had the best results was Solanum torvum fruit which pretreated by blanching process for 10 minutes at 70 ºC then dried by vacuum method at 50 ºC for 14 hours. The bioactive compounds content from Solanum torvum flour were Vitamin C 3.24 %, total phenol 85.16 mg·g-1, tannin 2.12 mg·g-1, flavonoids 9.10 mg·g-1, and antioxidant activity 92.1 %.